2014
DOI: 10.1016/j.ejca.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of oestrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 discordance between primary breast cancer and metastases

Abstract: Background: The discordance in oestrogen receptor (ER), progesterone receptor (PgR) and human epidermal growth factor receptor 2 (HER2) status between primary and recurrent breast cancer is being intensively investigated and a large amount of data have been produced. However, results from different studies are heterogeneous and often conflicting. To highlight this issue, a meta-analysis of published data was performed. Methods: A literature search was performed using Medline, and all the studies published from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
122
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(141 citation statements)
references
References 59 publications
15
122
0
4
Order By: Relevance
“…Today, assessment of HER2 status is based on tumor biopsy. However, HER2 expression can vary between the primary tumor and metastases in up to 40% of cases (2,5,6) and metastatic HER2 expression can change over time, which could necessitate a change of therapy (7,8). Follow-up using biopsies cannot always be performed due to practical reasons or patient discomfort.…”
mentioning
confidence: 99%
“…Today, assessment of HER2 status is based on tumor biopsy. However, HER2 expression can vary between the primary tumor and metastases in up to 40% of cases (2,5,6) and metastatic HER2 expression can change over time, which could necessitate a change of therapy (7,8). Follow-up using biopsies cannot always be performed due to practical reasons or patient discomfort.…”
mentioning
confidence: 99%
“…Detailed IHC study is the most helpful method in this case. Connel et al [9] compared the IHC findings between primary gastric malignancy and metastatic gastric malignancy from breast carcinoma. Highly significant proportions of metastatic breast carcinomas were positive for ER (72%), PR (33%), GCDFP (78%), and CK5/6 (61%) compared with primary gastric carcinomas (ER, 0%; PR, 0%; GCDFP, 0%; and CK5/6, 14%).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that a considerable controversy concerns the issue of hormone receptors (HRs) expression as well as HER2 status between primary breast carcinomas (BC) and metastatic sites from the same patient, as elsewhere reported in literature [1][2][3][4][5]. In particular, the discordance between primary BC and metastases from negative to positive and vice versa potentially affects the treatment regimen [5]; therefore, it has been suggested that neoplastic tissue of metastatic lesions should be systematically re-biopsied to optimally re-assess HR as well as HER2 [1,2,[4][5][6][7][8].In their meta-analysis, focusing on HER2 status, Aurilio et al documented that the pooled discordance proportion with respect to the primary breast tumour was 10% for distant metastases and 6% for loco-regional relapses. Moreover, a different pooled discordant proportion was found on the basis of the different utilised technique, since it was 10% in studies using immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH), but 5% in studies using IHC only; therefore, they conclude the observed discrepancy was not merely due to technicality.…”
mentioning
confidence: 99%
“…Nevertheless, whether these changes in HER2 status may be attributed to laboratory reproducibility in techniques or to other pre-analytical fac- tors, such as not standardised inadequate fixation or, otherwise, to biological modifications and heterogeneity in tumours, still remains to be clarified. On the other hand, the hypothesis that variation in HER2 status may reflect clonal genome evolution has been stressed [7]; consequently, tumour heterogeneity may be attributable to tumour biological trend leading to clonal selection with the development of new clones, previously undetectable within the primary breast cancer. In any case, the significant discordance between HER2 status in the comparison of primary and recurrent/metastatic breast carcinomas may influence the correct treatment, determining an inappropriate use of targeted therapies [8][9][10][11].…”
mentioning
confidence: 99%